Sentinel lymph node biopsy in high‐risk cutaneous squamous cell carcinoma of the head and neck: Systematic review and meta‐analysis. Issue 10 (17th June 2022) - Costantino, Andrea; Canali, Luca; Festa, Bianca Maria; Spriano, Giuseppe; Mercante, Giuseppe; De Virgilio, Armando
Abstract: The aim of our study was to better define the role of sentinel lymph node biopsy (SLNB) in high‐risk cutaneous squamous cell carcinoma of the head and neck (cSCCHN). A systematic review and meta‐analysis was performed according to the PRISMA statement. Seven‐hundred and five patients were included from 20 studies. The pooled SLN identification rate was 98.8% (95%CI: 97.0–99.8). The median number of SLN excised was 3.6 ( n  = 371, 95%CI: 2.0–4.4). The pooled SLNB positive rate and cumulative regional recurrence rate (RRR) in negative SLNB were 5.6% (95%CI: 2.6–9.6) and 2.9% (95%CI: 0.5–7.2), respectively. The high SLN identification rate demonstrates SLNB feasibility in cSCCHN. The low SLNB positive rate and the relatively high RRR raise some doubts concerning its clinical utility. Further studies are mandatory to define predictors of lymph node metastases able to better select patients that may benefit from a SLNB.